Argon-based atmospheric pressure plasma enhances early bone response to rough titanium surfaces - Coelho, Paulo G.; Giro, Gabriela [UNESP]; Teixeira, Hellen S.; Marin, Charles; Witek, Lukas; Thompson, Van P.; Tovar, Nick; Silva, Nelson R. F. A. (Wiley-Blackwell, 2012)
This study investigated the effect of an Argon-based atmospheric pressure plasma (APP) surface treatment operated chairside at atmospheric pressure conditions applied immediately prior to dental implant placement in a canine model. Surfaces investigated comprised: rough titanium surface (Ti) and rough titanium surface + Argon-based APP (Ti-Plasma). Surface energy was characterized by the Owens-Wendt-Rabel-Kaelble method and chemistry by X-ray photoelectron spectroscopy (XPS). Six adult beagles dogs received two plateau-root form implants (n = 1 each surface) in each radii, providing implants that remained 1 and 3 weeks in vivo. Histometric parameters assessed were bone-to-implant contact (BIC) and bone area fraction occupancy (BAFO). Statistical analysis was performed by Kruskall-Wallis (95% level of significance) and Dunn's post-hoc test. The XPS analysis showed peaks of Ti, C, and O for the Ti and Ti- Plasma surfaces. Both surfaces presented carbon primarily as hydrocarbon (C?C, C?H) with lower levels of oxidized carbon forms. The Ti-Plasma presented large increase in the Ti (+11%) and O (+16%) elements for the Ti- Plasma group along with a decrease of 23% in surface-adsorbed C content. At 1 week no difference was found in histometric parameters between groups. At 3 weeks significantly higher BIC (>300%) and mean BAFO (>30%) were observed for Ti-Plasma treated surfaces. From a morphologic standpoint, improved interaction between connective tissue was observed at 1 week, likely leading to more uniform and higher bone formation at 3 weeks for the Ti-Plasma treated implants was observed. (C) 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A 2012.
Keywords: endosseous implant; surface treatment; atmospheric pressure plasma plasma; osseointegration